Prospects for the study of Kazakhstani plant species of the genus Linum L. - Omarkhan Aktoty Berikkyzy; Zhumashova Gulsim Tokanovna; Sakipova Zuriyadda Bektemirovna (Research Retrieval and Academic Letters, 2025)
Linum L. species are the oldest cultivated plants and belong to the family Linaceae Dumort. The plants belong to the class of Magnoliopsida, the order of Linales. The order of Linales includes two families - Erythroxylaceae and Linaceae. The family of Linaceae has 9 genus and 274 species according to the APG IV (Angiosperm Phylogeny Group IV system of flowering plant classification). Such biologically active substances as lignans, polyunsaturated fatty acids, flavonoids, phenolic acids, amino acids, phenylpropanoid glucosides and essential oils have been isolated from Linum plants. The most widespread and studied species of Linum plants is the Linum usitatissimum L. This ancient world plant has found wide application in many countries in medicine and industry. In medicine, Linum usitatissimum is promising in dealing with cardiovascular, genitourinary, and respiratory diseases, as well as gastrointestinal disorders [1-2].